Safety and efficacy of ferric carboxymaltose in management of iron deficiency anemia in pregnant and peripartum women - Bhudhrani, Divyang S.; Godria, Payal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Anemia during pregnancy, often attributed to iron deficiency, poses substantial risks to both maternal and fetal health. This retrospective study aims to evaluate the safety and efficacy of intravenous ferric carboxymaltose (FCM) in managing anemia among pregnant women. Methods: The study encompasses women who received FCM treatment for anemia during pregnancy between October 2023 and March 2024 at SSG hospital, Vadodara. Key outcomes evaluated include maternal safety and pregnancy outcomes. Prospective observational study; Treatment effectiveness was assessed by repeat hemoglobin (Hb) measurements and patient report of well-being in the postpartum period. Safety was assessed by analysis of adverse drug reactions and fetal heart rate monitoring during the infusion. Results: A total of 50 patients were included. The intravenous administration of FCM notably raised hemoglobin levels in all pregnant female participants compared to initial levels. Monitoring of fetal heart rate showed no adverse effects attributable to the medication. No severe side effects were observed. Conclusions: This prospective observational study suggests that FCM represents a safe and effective therapeutic option for managing anemia during pregnancy. Despite study limitations, the findings underscore the potential of FCM in addressing this prevalent concern, advocating for its consideration in clinical practice.